Features of the dynamic properties of the working bodies of technological machines with inertial excitation of vibrations - Andrey V. Eliseev; Vladimir B. Kashuba; Nikita Z. Kinash; Sergey V. Eliseev (Advanced Engineering Research, 2016)
The methodological basis for an estimation of the dynamic properties of a technological vibrating complex is offered. The selection rationale of parameters is made through the structural mathematical model approaches. The automatic control system architecture equivalent in the dynamic relation to the settlement scheme in the form of a solid body with elastic supports is developed as part of this approach. The structural mathematical modeling for the analysis and dynamic synthesis problems involves using the system transfer functions. The concept of the transfer function of linearized connections which interpretation specifies the conditions for the implementation of the necessary distribution of the vibration amplitudes or the form of oscillating field is introduced. The choice of the working conditions of the technological complex is characterized by such a distribution of the mechanical oscillating system parameters when points of a certain area of the vibrostand work table are reduced to a mode or a state of dynamic oscillatory damping. The design procedure of the parameters providing necessary dynamic interactions of the system elements is offered. The sequence of actions for selecting values of the vibrostand baricentric parameters is developed; analytical relations for the definition of frequencies and the corresponding frequency characteristics are obtained.